Estratégias de aprendizagem utilizadas por estudantes cegos - Lins, Manuela Ramos Caldas (2011)
Learning strategies can be understood as a planned sequence of procedures or activities, selected in order to facilitate the acquisition, storage and use of information. Although important to the learning process, the knowledge on these strategies is still insufficient, especially with regard to students with visual impairments. Therefore, this study aimed to characterize learning strategies used by blind and sighted students, registered in elementary education in schools and special institutions. Were participants 23 teachers, male and female, aged between 26 and 51 years, and 102 students, of whom 25 were blind and 77 seers, of both genders, registered on the 3rd to the 9th grade of elementary school, aged 7 to 16 years old. The instruments used were: field diary (students and teachers); structured questionnaire (teachers); sociodemographic questionnaire, interview and Assessment Scale of Learning Strategies for Elementary School (students). Initially were made observations in the classroom and the teachers received the questionnaires, with instructions for completion. Then were made the interviews with blind students and the scale was administered with these and with the seers. All instruments were administered individually. We conducted content analysis of the questionnaires with teachers and the interviews with blind students. The scale of strategies and sociodemographic questionnaire were analyzed with the help of descriptive and inferential statistics. It was noticed that the blind students use few learning strategies in the classroom, regardless of city, series, sex or age. It was found that teachers didn t receive training to deal with blind students, either during graduation or after have completed it, in such a way that few of them were able to inform about the learning strategies the students use, and demonstrated low ability to deal with these inefficiencies. It was also found that the blind and the sighted use cognitive and metacognitive strategies during learning, but those used by the blind seem to be more basic, low complexity, given that the seers have achieved higher scores on all subscales. We conclude that the repertoire of learning strategies for blind students is inflexible, requiring increments so that they can achieve significant results. It is important that teachers receive training to understand the learning strategies and how they positively influence learning